2022
DOI: 10.1111/jgs.18104
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium after transcatheter aortic valve replacement: An updated systematic review and meta‐analysis

Abstract: Aims To perform an updated systematic review and meta‐analysis of postoperative delirium (POD) after transcatheter aortic valve replacement (TAVR). Methods We conducted a systematic literature search of PubMed, Embase, and Cochrane Library databases from the time of the first human TAVR procedure in 2002 until December 24, 2021, which was supplemented by manual searches of bibliographies. Data were collected on incidence rates, risk factors, and/or associated mortality of POD after TAVR. Pooled analyses were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 95 publications
0
1
0
Order By: Relevance
“…In our meta-regression analysis, the absence of age and sex influences on the GA-POD link is interesting. Advanced age and male sex are well-established risk factors for POD based on previous research 11 . The lack of association in this meta-regression analysis suggests that GA exposure may increase the risk of POD regardless of age and sex in patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In our meta-regression analysis, the absence of age and sex influences on the GA-POD link is interesting. Advanced age and male sex are well-established risk factors for POD based on previous research 11 . The lack of association in this meta-regression analysis suggests that GA exposure may increase the risk of POD regardless of age and sex in patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 97%
“…Besides inflammatory response that has been proposed to be a contributor to POD 7 , several modifiable and non-modifiable risk factors were identified in a recent large-scale meta-analysis of 69 studies focusing on patients undergoing TAVR without exposure to surgery-induced inflammatory response 11 . Non-modifiable predisposing factors included advanced age, prior stroke/transient ischemic attack, male gender, and postoperative acute kidney injury, atrial fibrillation/flutter, and impaired Instrumental Activities of Daily Living 11 , while modifiable risk factors consisted of GA exposure, weight loss, electrolyte imbalance, and techniques of TAVR (e.g., www.nature.com/scientificreports/ non-transfemoral Access) 11 . Despite the inclusion of up to 69 studies in that meta-analysis, it involved only nine studies with 3,555 patients when assessing the impact of GA on the risk POD 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2021 meta-analysis by Chen et al analysing 14 studies with a total sample size of 13,286, the following risk factors for postoperative delirium in cardiac surgery patients were identified: age, carotid artery stenosis, depression, diabetes, NYHA functional class III or IV, duration of mechanical ventilation and length of ICU stay [17]. In their 2022 meta-analysis on postoperative delirium after transcatheter aortic valve replacement, Ma et al identified the following risk factors for delirium: increased age, male sex, prior stroke or TIA, atrial fibrillation/flutter, weight loss, electrolyte abnormality, general anaesthesia and postoperative acute kidney injury [18]. Similarly, in our study, older age and worse overall preoperative condition were found to be associated with a higher incidence of postoperative delirium.…”
Section: Discussionmentioning
confidence: 99%